Identification and functional prediction of stress responsive AP2/ERF transcription factors in Brassica napus by genome-wide analysis. (December 2017) - Owji, Hajar; Hajiebrahimi, Ali; Seradj, Hassan; Hemmati, Shiva
Graphical abstract: Highlights: By implementing genome-wide analysis, 321 AP2/ERF transcription factors were identified in Brassica napus . BnAP2/ERFs were formed through duplication events, occurring before Brassica napus formation. The BnERF039 and BnERF245 are candidates for improving salt-tolerant Brassica napus . BnERF227, BnERF228, BnERF234, BnERF134, BnERF132, BnERF176, and BnERF235 are candidates for improving Leptosphaeria- tolerant Brassica napus . Abstract: Using homology and domain authentication, 321 putative AP2/ERF transcription factors were identified in Brassica napus, called BnAP2/ERF TFs. BnAP2/ERF TFs were classified into five major subfamilies, including DREB, ERF, AP2, RAV, and BnSoloist. This classification is based on phylogenetic analysis, motif identification, gene structure analysis, and physiochemical characterization. These TFs were annotated based on phylogenetic relationship with Brassica rapa . BnAP2/ERF TFs were located on 19 chromosomes of B. napus. Orthologs and paralogs were identified using synteny-based methods Ks calculation within B. napus genome and between B. napus with other species such as B. rapa, Brassica oleracea, and Arabidopsis thaliana indicated that BnAP2/ERF TFs were formed through duplication events occurred before B. napus formation. Kn/Ks values were between 0 and 1, suggesting the purifying selection among BnAP2/ERF TFs. Gene ontology annotation, cis -regulatory elements and functional interaction networks suggested that BnAP2/ERF TFs participate in response to stressors, including drought, high salinity, heat and cold as well as developmental processes particularly organ specification and embryogenesis. The identified cis- regulatory elements in the upstream of BnAP2/ERF TFs were responsive to abscisic acid. Analysis of the expression data derived from Illumina Hiseq 2000 RNA sequencing revealed that BnAP2/ERF genes were highly expressed in the roots comparing to flower buds, leaves, and stems. Also, the ERF subfamily was over-expressed under salt and fungal treatments. BnERF039 and BnERF245 are candidates for salt-tolerant B. napus . BnERF253-256 and BnERF260-277 are potential cytokinin response factors. BnERF227, BnERF228, BnERF234, BnERF134, BnERF132, BnERF176, and BnERF235 were suggested for resistance against Leptosphaeria maculan and Leptosphaeria biglobosa .